Internalized Stigma in Pediatric Psoriasis: A Comparative Multicenter Study - (:unkn) unknown (KOREAN DERMATOLOGICAL ASSOC, 2020)
Background: Internalized stigma, adoption of negative attitudes and stereotypes of the society regarding persons' illness, has not been studied previously in pediatric psoriasis patients. Objective: We aimed to investigate the internalized stigma in pediatric psoriasis patients and to determine differences according to factors affecting internalized stigma compared to adult psoriasis patients. Methods: This multicenter, cross-sectional, comparative study included 125 pediatric (55 female, 70 male; mean age +/- standard deviation [SD], 14.59 +/- 2.87 years) and 1,235 adult psoriasis patients (577 female, 658 male; mean age +/- SD, 43.3 +/- 13.7 years). Psoriasis Internalized Stigma Scale (PISS), Dermatology Life Quality Index (DLQI), Perceived Health Status (PHS), and the General Health Questionnaire (GHQ)-12 were the scales used in the study. Results: The mean PISS was 58.48 +/- 14.9 in pediatric group. When PISS subscales of groups were compared, the pediatric group had significantly higher stigma resistance (p = 0.01) whereas adult group had higher scores of alienation (p = 0.01) and stereotype endorsement (p = 0.04). There was a strong correlation between mean values of PISS and DLQI (r = 0.423, p = 0.001). High internalized stigma scores had no relation to either the severity or localization of disease in pediatric group. However, poor PHS (p = 0.007) and low-income levels (p = 0.03) in both groups, and body mass index (r = 0.181, p = 0.04) in the pediatric group were related to high PISS scores. Conclusion: Internalized stigma in pediatric patients is as high as adults and is related to poor quality of life, general health, and psychological illnesses. Unlike adults, internalized stigma was mainly determined by psoriasis per se, rather than disease severity or involvement of visible body parts, genitalia or folds.
Keywords: Child; Inflammation; Psoriasis; Quality of life; Stigmatization; PSYCHOMETRIC PROPERTIES; PERCEIVED STIGMA; MENTAL-ILLNESS; D PERSONALITY; STIGMATIZATION; RELIABILITY; PREDICTORS; SEVERITY; VALIDITY; DISEASE